1970
DOI: 10.1021/bi00824a014
|View full text |Cite
|
Sign up to set email alerts
|

γ-Butyrobetaine hydroxylase from Pseudomonas sp AK 1

Abstract: A soluble y-butyrobetaine hydroxylase has been partially purified from cells of a Pseudomonas strain (Pseudomonas sp AK 1) by chromatography on DEAE-cellulose and on hydroxylapatite. Carnitine is the only product of y-butyrobetaine; trimethylamine or trimethylaminoacetone is not formed. The enzyme has a low isoelectric point (around pH 4.5). The K M ,~~~ value for y-butyrobetaine is 2.4 mM. There is an absolute and specific requirement for 2-ketoglutarate and I n the previous studies of carnitine metabolism, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1973
1973
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…The enzyme has been isolated in homogeneous form from Pseudomonas sp. AK1 [17] and calf liver [18]. The properties of γ‐butyrobetaine hydroxylase from different sources are similar [19].…”
Section: L‐(−)‐carnitine Degradation Under Aerobic Conditionsmentioning
confidence: 99%
“…The enzyme has been isolated in homogeneous form from Pseudomonas sp. AK1 [17] and calf liver [18]. The properties of γ‐butyrobetaine hydroxylase from different sources are similar [19].…”
Section: L‐(−)‐carnitine Degradation Under Aerobic Conditionsmentioning
confidence: 99%
“…Therefore, many studies reported the enhancement of g-BBD and TMLD activity upon the addition of VC in a dose-dependent manner using tissue extracts or partially purified enzymes. [18][19][20][21][22][26][27][28] In the absence of VC, however, g-BBD activity was detected by adding glutathione peroxidase and glutathione (GSH) to the reaction mixture, 29) although this test was not performed for TMLD.…”
mentioning
confidence: 99%
“…Gamma-butyrobetaine is hydroxylated into L-carnitine in a reaction, which requires alpha-ketoglutarate, oxygen, ascorbic acid, and Fe 2þ by gamma-butyrobetaine hydroxylase (EC.1.14.1.1). [26][27][28][29][30] The pathways involved in the degradation of TMA-Butanol have been studied in Pseudomonas sp. 13CM.…”
Section: Reagentmentioning
confidence: 99%